2011
DOI: 10.4049/jimmunol.1004181
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus-Specific CD4+ T Cells Exhibit Reduced STAT-5 Signaling and Altered Cytokine Profiles in Patients with Recurrent Respiratory Papillomatosis

Abstract: Recurrent Respiratory Papillomatosis (RRP) is caused by HPV-6 or -11. Specific HLA-DR haplotypes, DRB1*01:02 and DRB1*03:01 are associated with the development of RRP, disease severity, and TH2-like responses to HPV early proteins. TH1-like responses to HPV proteins have been shown to be protective in animal models. Therefore, we investigated the hypothesis that RRP patients have dysfunctional TH1-like HPV-specific T-cell responses. Using MHC class II tetramers, we identified immunogenic peptides within HPV-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Monitoring immunity to infectious pathogens. Class II tetramers have been used for analysis of a variety of human CD4 T cell responses to pathogens, including influenza A, Borrelia, EBV, CMV, Mycobacterium tuberculosis, human T-lymphotropic virus 1, hepatitis C, anthrax, severe acute respiratory syndrome virus, human papillomavirus, and HIV (3,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Ag-specific T cells are detected in peripheral blood, with a very broad range of frequency, depending on prior Ag exposure, vaccination history, and timing of immunization.…”
Section: Rare Cd4 T Cell Detection Using Class II Pmhc Tetramersmentioning
confidence: 99%
“…Monitoring immunity to infectious pathogens. Class II tetramers have been used for analysis of a variety of human CD4 T cell responses to pathogens, including influenza A, Borrelia, EBV, CMV, Mycobacterium tuberculosis, human T-lymphotropic virus 1, hepatitis C, anthrax, severe acute respiratory syndrome virus, human papillomavirus, and HIV (3,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Ag-specific T cells are detected in peripheral blood, with a very broad range of frequency, depending on prior Ag exposure, vaccination history, and timing of immunization.…”
Section: Rare Cd4 T Cell Detection Using Class II Pmhc Tetramersmentioning
confidence: 99%
“…Among different gene network motifs, an incoherent type 1 feed forward loop is known to create a pulse-like transient behavior and it is unlikely that cells utilize a negative feedback motif to generate such behavior [29]. Furthermore, a recent study reports that pSTAT5 may increase IL-2 secretion indicating that there can also be a positive feedback mechanism involved [30]. …”
Section: Resultsmentioning
confidence: 99%
“…First, negative feedback is not appropriate for generating a pulse-like, transient behavior [29]. Second, both negative and positive feedback mechanisms have been reported [30] and these mechanisms may be differentially used under different conditions although they are not completely understood [11]. Third, the negative feedback model cannot explain the termination of IL-2 production/secretion in the presence of sustained antigenic stimulus [26].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the balance of proinflammatory vs. anti-inflammatory immune mediators and cells within the papilloma microenvironment is altered to support persistence of HPV6/11 infection, following activation of latent infection, with subsequent papilloma recurrence (8,(11)(12)(13)(14)(15). We previously showed that T-cell responses to autologous papilloma tissue and to HPV6/11 early proteins are polarized away from effective viral control (8,11,14), likely secondary to functional PD1 + /CD4 + Tregs in these lesions (15). In addition, CD8 + /CD28 − T cells that express granzyme are present in papillomas but fail to function as mature cytotoxic T lymphocytes (CTLs) (8).…”
Section: Introductionmentioning
confidence: 99%